(3OQGSI hJMdjd GdejRGfjI HGSJYeGd GdeDTQGJ hGdfSH GdeGdjI (B:s (3eQab HJeGQjf eMdhdI (B/s - (3HhjHGhf, eSYhOs ((3GdLRGFQ (B: s (3OGQ EjdjGA ddfTQ hGdJhRjY(B, s, 2024)
(3OQGSI h JMdjd GdejRGfjI eaghe GdejRGfjI h eVehfgG GdGfJbGd ef GdejRGfjI GdeMGSHjI Gdi GdejRGfjI GdeGdjI GjVG GdejRGfjI GdeGdjI h GdejRGfjI GdeGdjI GdeNJUQI , GdeDTQGJ GdeGdjI JMJhj Jbjje GdGOGA GdeGdj JMdjd GdejRGfjI HGSJNOGe GdeDTQGJ GdeGdjI , GdfSH GdeGdjI GdGWGQ GdfXQj ddfSH GdeGdjI h JMdjd GdejRGfjI HGSJNOGe GdfSH GdeGdjI (B.s
(3GdeQGLY U(B.155-162s
Keywords: (3GdejRGfjIs